Analysis of variation of serum CEA, SCC, CYFRA21-1 in patients with lung cancer and their diagnostic value with EBUS-TBNA - Du, YanJia; Wen, Ya; Huang, JieYu (Journal of Medical Biochemistry, 2023)
Objective: To explore the variation of serum carcinoembryonic antigen (CEA), cytokeratin 19 fragment (CYFRA21-1) and squamous cell carcinoma (SCC) antigen in patients with lung cancer (LC) and their diagnostic value with endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA). Methods: Selection of 150 patients with suspected lung malignant lesions as the research objects was to analyze the diagnostic value of serum tumor marker test and EBUS-TBNA joint detection for LC. Results: The AUC of joint examination to diagnose LC and identify pathological types of LC was elevated vs. alone detection of each index. Conclusions: Serum CYFRA21-1, SCC and CEA conjugating with EBUS-TBNA are provided with diagnostic value for LC and identified value for pathological types of LC.